2016
DOI: 10.15171/jrip.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Administration of pentoxifylline to improve anemia of hemodialysis patients

Abstract: Introduction: One of the most important causes of erythropoietin-resistant anemia in end-stage renal disease (ESRD) patients is increased levels of inflammatory cytokines. Objectives: In this study pentoxifylline, an anti-inflammatory and anti-cytokine drug, with no significant side effects was used to manage anemia in ESRD patients. Patients and Methods: Thirty-nine ESRD patients with erythropoietin-resistant anemia were assigned to two groups, the treatment and the control groups. In treatment group, 19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…That was in agreement with Gonzalez-Espinoza and colleagues [21] that showed a significant reduction in all inflammatory markers named CRP, IL-6, and TNF-alfa in the treatment group by the end of the study. In our study, serum albumin increased significantly in the treatment group in agreement with the study conducted by Shahbazani et al, [8] in 2017. On the other hand, the study conducted by Antunes and colleagues (2014) [26] showed no significant changes in serum albumin or CRP between both groups at the end of the study.…”
Section: Moreover Cooper and Colleaguessupporting
confidence: 93%
See 3 more Smart Citations
“…That was in agreement with Gonzalez-Espinoza and colleagues [21] that showed a significant reduction in all inflammatory markers named CRP, IL-6, and TNF-alfa in the treatment group by the end of the study. In our study, serum albumin increased significantly in the treatment group in agreement with the study conducted by Shahbazani et al, [8] in 2017. On the other hand, the study conducted by Antunes and colleagues (2014) [26] showed no significant changes in serum albumin or CRP between both groups at the end of the study.…”
Section: Moreover Cooper and Colleaguessupporting
confidence: 93%
“…However, they selected patients with Hb <10.7 despite receiving an ESA dose equal to or more than 12000IU /week. On the other hand, Shahbazian et al, [8] reported a higher percent than ours. They found that 53% of their HD patients had anemia despite sufficient iron stores and appropriate ESA dose after exclusion of known causes of ESA hyporesponsiveness.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The presence of anemia in hemodialysis patients can increase the mortality rate in this group of patients (3). It can cause fatigue, asthenia, and dyspnea, however, in some cases, the symptoms of anemia may quickly develop with higher intensity (4). Anemia, a symptom of chronic kidney disease (CKD), is one of the most important indices that can be related to many interfering factors (5).…”
Section: Introductionmentioning
confidence: 99%